Involvement of non-coding RNAs in chemotherapy resistance of ovarian cancer - Shao, Yang (J Cancer, 2018)
Ovarian cancer (OC) is the most lethal gynecological malignancy, with a low 5-year survival rate. Most patients with ovarian cancer are diagnosed in late-stages. A rising number of non-coding RNAs (ncRNAs) have been found to act as key regulators of gene expression by applying novel high-thought methods, such as next generation sequencing (NGS). Non-coding RNAs not only play important roles in carcinogenesis, but also affect the clinical treatment strategies. One of the biggest challenge in OC treatment was chemoresistance, which causes poor prognosis and high recurrence rate after applying traditional remedies. Of note, it has been proved that ncRNAs were deeply correlated with chemoresistance in several cancers, which made ncRNAs considered to be potential therapeutic targets in ovarian cancer. Among of all ncRNAs, the studies of miRNAs and lncRNAs in ovarian cancer chemoresistance were much clearer. In this study, we reviewed the most relevant researches in this field, and described the relationships between ncRNAs and chemoresistance in ovarian cancer.